Genetic surfing during the range expansion of an endangered large carnivore - Laura Tensen; Mathias Currat; Harriet Davies-Mostert; Cole du Plessis; Klaus Fischer (Biodiversity and Conservation, 2024)
In an effort to halt the global decline of large carnivores, reintroductions have become increasingly popular to establish satellite populations and reduce the risk of stochastic events. These artificial range expansions are typically formed by a small number of founders, which can lead to changes in population genetic structure. For instance, serial founder events can lead to neutral and even deleterious alleles reaching higher than expected frequencies along the front end of an expansion, referred to as gene surfing. One of the world’s most extensive range expansion programmes has been for endangered African wild dogs ( Lycaon pictus ). In this study, we examine the effect of continent-wide translocations on spatial genetic diversity, by determining what effect genetic surfing has on population structure in wild dogs, and measuring how long it will take for population structure to homogenize in the face of ongoing dispersal. We used a set of microsatellite loci to look at surfing alleles in five populations across southern Africa, and simulated the movement of these alleles forward in time under the current demographic scenario. We found that it would take about 150 generations for the expanding population to be 50% introgressed with genes from the free-roaming population. With the current rate of translocations, genetic differentiation in southern Africa will disappear, overturning the effects of genetic drift or surfing alleles. Understanding genetic patterns in expanding populations is of great interest to conservation, and we demonstrate that reintroduction programmes can help restore genetic diversity, and consequently adaptive potential, in recovering wildlife populations.

Influence of Paleolithic range contraction, admixture and long‐distance dispersal on genetic gradients of modern humans in Asia - Catarina Branco; Nicolas Ray; Mathias Currat; Miguel Arenas (Molecular Ecology, 2020)
Cavalli‐Sforza and coauthors originally explored the genetic variation of modern humans throughout the world and observed an overall east‐west genetic gradient in Asia. However, the specific environmental and population genetics processes causing this gradient were not formally investigated and promoted discussion in recent studies. Here we studied the influence of diverse environmental and population genetics processes on Asian genetic gradients and identified which could have produced the observed gradient. To do so, we performed extensive spatially‐explicit computer simulations of genetic data under the following scenarios: (a) variable levels of admixture between Paleolithic and Neolithic populations, (b) migration through long‐distance dispersal (LDD), (c) Paleolithic range contraction induced by the last glacial maximum (LGM), and (d) Neolithic range expansions from one or two geographic origins (the Fertile Crescent and the Yangzi and Yellow River Basins). Next, we estimated genetic gradients from the simulated data and we found that they were sensible to the analysed processes, especially to the range contraction induced by LGM and to the number of Neolithic expansions. Some scenarios were compatible with the observed east‐west genetic gradient, such as the Paleolithic expansion with a range contraction induced by the LGM or two Neolithic range expansions from both the east and the west. In general, LDD increased the variance of genetic gradients among simulations. We interpreted the obtained gradients as a consequence of both allele surfing caused by range expansions and isolation by distance along the vast east‐west geographic axis of this continent.

Effect of hybridization with genome exclusion on extinction risk - Claudio S. Quilodrán; Mathias Currat; Juan I. Montoya‐Burgos (Conservation Biology, 2018)
Human‐induced habitat changes may lead to the breakdown of reproductive barriers between distantly related species. This phenomenon may result in fertile first‐generation hybrids (F 1 ) that exclude the genome of one parental species during gametogenesis, thus disabling introgression. The species extinction risk associated with hybridization with genome exclusion is largely underappreciated because the phenomenon produces only F 1 hybrid phenotype, leading to the misconception that hybrids are sterile and potentially of minor conservation concern. We used a simulation model that integrates the main genetic, demographic, and ecological processes to examine the dynamics of hybridization with genome exclusion. We showed that this mode of hybridization may lead to extremely rapid extinction when the process of genome exclusion is unbalanced between the interbreeding species and when the hybridization rate is not negligible. The coexistence of parental species was possible in some cases of asymmetrical genome exclusion, but show this equilibrium was highly vulnerable to environmental variation. Expanding the exclusive habitat of the species at risk allowed its persistence. Our results highlight the extent of possible extinction risk due to hybridization with genome exclusion and suggest habitat management as a promising conservation strategy. In anticipation of serious threats to biodiversity due to hybridization with genome exclusion, we recommend a detailed assessment of the reproductive status of hybrids in conservation programs. We suggest such assessments include the inspection of genetic content in hybrid gametes.

Recipient of the 2013 Molecular Ecology Prize: Laurent Excoffier - Daniel Wegmann; Mathias Currat (Molecular Ecology, 2014)

Colonization history of the Swiss Rhine basin by the bullhead ( Cottus gobio ): inference under a Bayesian spatially explicit framework - SAMUEL NEUENSCHWANDER; CARLO R. LARGIADÈR; NICOLAS RAY; MATHIAS CURRAT; PASCAL VONLANTHEN; LAURENT EXCOFFIER (Molecular Ecology, 2008)
The present distribution of freshwater fish in the Alpine region has been strongly affected by colonization events occurring after the last glacial maximum (LGM), some 20 000 years ago. We use here a spatially explicit simulation framework to model and better understand their colonization dynamics in the Swiss Rhine basin. This approach is applied to the European bullhead ( Cottus gobio ), which is an ideal model organism to study fish past demographic processes since it has not been managed by humans. The molecular diversity of eight sampled populations is simulated and compared to observed data at six microsatellite loci under an approximate Bayesian computation framework to estimate the parameters of the colonization process. Our demographic estimates fit well with current knowledge about the biology of this species, but they suggest that the Swiss Rhine basin was colonized very recently, after the Younger Dryas some 6600 years ago. We discuss the implication of this result, as well as the strengths and limits of the spatially explicit approach coupled to the approximate Bayesian computation framework.